Implementation of Digital Marketing in Micro, Small, Medium Enterprises (UMKM) in Bagon Village as a Modernization Step For Community Economic Empowerment - Nur Andita Prasetyo; M Faiz Firdausi; Iqbal Sabilirrasyad; Mas'ud Hermansyah (RECORD: Journal of Loyality and Community Development, 2024)
The economic industry is experiencing a new era in all aspects. The digital era has replaced the conventional era in the economic industry. The economic industry is experiencing changing times, including in terms of marketing. The digital marketing era that is starting to develop requires economic players to change and keep up with the times. MSME economic actors in Bagon Village are no exception, the 023 Collaborative KKN Group, which is aware of the changes in the industrial economic era, invites MSME actors in Bagon Village to modernize the economy. Modernization of the MSME economy in Bagon Village includes the implementation of digital marketing for micro businesses. This work program was designed based on the results of a survey by KKN-K Group 023 students who directly observed MSME actors in Bagon Village. Therefore, KKN-K Group 023 students invited Bagon Village MSMEs to take part in this work program through training and elaboration of work programs related to digital marketing including product branding, creating e-commerce accounts, and promotion on social media. Not only that, the output produced from this activity can also have a positive impact on Bagon Village MSMEs and also MSME products that are the target of the activity work program